PTU-031 Downregulation of the vitamin B12 receptor in fibrolamellar carcinoma of the liver: the first consistent molecular abnormality. (28th May 2012) - Johnson, P; Baldwin, G; Teng, M; O'Sullivan, B; James, J; Brundler, M-A; Taniere, P
Abstract : Introduction: Fibrolamellar hepatocellular carcinoma (FLHCC) is a rare tumour of young adults that is characterised by the presence of large tumour cells with strongly eosinophilic cytoplasm, surrounded by fibrous lamellae, in the absence of chronic liver disease. No consistent molecular abnormalities have been detected to date but an elevation of serum vitamin B12 binding capacity has been described. Methods: Up to 80% of vitamin B12 (cobalamin), is stored in the liver after endocytosis via the transcobalamin receptor (CD320). We hypothesised that disruption to the transcobalamin receptor (hereafter referred to as CD320) might render the liver locally B12 deficient and elicit a compensatory production of the serum B12 binding protein (TCN1). We sought a functional mutation of CD320 in 15 cases of FLHCC and 30 cases of conventional hepatocellular carcinoma (HCC), 10 cases with cirrhosis (C-HCC) and 20 cases with no cirrhosis (NC-HCC)) acting as control tissues. cDNA was synthesised using RNA purified from formalin fixed paraffin embedded (FFPE) tissues and primers were designed to amplify the region spanning exon2/3 across the mutation site. Results: Sequencing analysis showed ∼5% (1/18) mutation in NC HCC. However, 60% (9/15) of the FLHCC cohort did not show any amplification while 80% of NC-HCC (16/20) and C-HCC (8/10) tumours tested positive. The quality of purified mRNA was verified by amplifying for two different housekeeping genes, tubulin and β-glucuronidase. To determine the reason for non-amplification of CD320exon2/3, we sequenced the promoter and promoter regulator region of CD320 using DNA purified from FFPE tissue. Comparison of the sequences of CD320 (+) and (−) representative samples showed no difference in their DNA sequence. Methylation analysis of the methylation sensitive promoter regulator region of NC-HCC, and FLHCC showed a correlation between the level of methylation and CD320 suppression in NC-HCC but not for FLHCC. To address this discrepancy, a second region of CD320, spanning exon3/4 was amplified. Interestingly, all the FLHCC samples were positive giving an amplification product for this region. Immunostaining for CD320 was in agreement with the exon 3/4 amplification data. Conclusion: Taken together, these results indicate that the expression of a non-functional splice variant (variant 2), which lacks the crucial triple glutamic acid repeat within the exon 2 necessary for the receptor's function, may contribute to the increased serum Vitamin B12 binding capacity in FLHCC. Competing interests: None declared.